Measurement of the integrated and differential $t \bar t$ production cross sections for high-$p_t$ top quarks in $pp$ collisions at $\sqrt s =$ 8 TeV - CMS collaboration (2294 authors); Calpas, Betty; Nayak, Aruna; Bargassa, Pedrame; Beirão Da Cruz E Silva, Cristóvão; Di Francesco, Agostino; Faccioli, Pietro; Ferreira Parracho, Pedro Guilherme; Gallinaro, Michele; Hollar, Jonathan; Leonardo, Nuno; Lloret Iglesias, Lara; et al. (My University, 2016)
The cross section for pair production of top quarks (tt¯) with high transverse momenta is measured in pp collisions, collected with the CMS detector at the LHC with s=8  TeV in data corresponding to an integrated luminosity of 19.7  fb-1. The measurement is performed using lepton+jets events, where one top quark decays semileptonically, while the second top quark decays to a hadronic final state. The hadronic decay is reconstructed as a single, large-radius jet, and identified as a top quark candidate using jet substructure techniques. The integrated cross section and the differential cross sections as a function of top quark pT and rapidity are measured at particle level within a fiducial region related to the detector-level requirements and at parton level. The particle-level integrated cross section is found to be σtt¯=0.499±0.035(stat+syst)±0.095(theo)±0.013(lumi)  pb for top quark pT>400  GeV. The parton-level measurement is σtt¯=1.44±0.10(stat+syst)±0.29(theo)±0.04(lumi)  pb. The integrated and differential cross section results are compared to predictions from several event generators.